Pengembangan Sikap Keberagamaan Peserta Didik - Sutarto, Sutarto (Sekolah Tinggi Agama Islam (STAIN) Curup, 2018)
This paper aims to reveal the nature of religious attitudes, factors that affect the attitude of religious, characteristics and development, the components and forms and how to develop the attitude of religious learners. The method used is library research and analyzed by reflective thinking. Based on the findings can be seen that the attitude of religious learners basically an internal state that exists in the learners that formed through interaction with the environment. The characteristics and development of the religious attitudes of each learner vary according to the stages of development. These differences can be seen from the cognitive, affective and conative aspects. Establishment and development of a stance must begin early and be done according to their cognitive characteristics, emotions and level of consciousness. There are two ways that can be done to grow and develop the attitude of religious learners, namely: First, the internalization of Islamic values. Internalization of Islamic values can be done by giving exemplary, suggestive and correction and social impulse. Second, creating a religious environment in the family, school and community.